Reflections on communication in intercultural organizations from a sustainable perspective - Fernandes, Érik Álvaro; Marchiori, Marlene (Organicom, 2014)
With globalization, organizations are, simultaneously, intercultural agents and spaces that demanding subjects in intercultural process. In this dynamic are implicit challenges that require the participation of the individual of interaction, which has the communication as a producer of meanings in building intercultural organizational realities. In this context, the demands from sustainability arising, which require individual in intercultural negotiation processes to preserve the future. Thus, this theoretical essay aims to show ways to the demands of these spheres.